Improving Soccer Players' Memorization of Soccer Tactics: Effects of Visual Realism, Soccer Expertise, and Visuospatial Abilities. Issue 3 (June 2022) - Mahfoudh, Hatem Ben; Zoudji, Bachir
In this study, we aimed to examine the effect of visual realism on soccer players' memorization of soccer tactics according to their level of expertise and visuospatial abilities. We divided 48 volunteers into novice and expert soccer players and had them first perform a multitask visuospatial abilities (VSA) test and then undergo training with three dynamic soccer scenes, each presented with varied levels of realism (schematic, moderately realistic, and highly realistic). We then tested players' memorization and reproduction of the soccer scenes and measured their visual processing with eye-tracking glasses to identify their cognitive processes during memorization. We found that reducing visual realism improved visual processing and memorization when compared to higher realism ( p < .001). Second, both higher (vs. lower) player expertise and higher (vs. lower) VSA influenced visual processing and enhanced memorization efficiency ( p < .001). Third, there were significant interaction effects between visual realism, player expertise, and player VSA ( p < .001) such that players with high VSA benefited more from reduced (vs. accentuated) visual realism than did players with low VSA. Thus, increasing visual realism can hinder tactical learning effectiveness, especially for learners who lack domain expertise and visuospatial abilities. Practically speaking, coaches and educators might improve their communications by tailoring tactical instructions to learners' cognitive skills.